Gellan gum-based hydrogel bilayered scaffolds for osteochondral tissue engineering - Pereira, D. R. (2014)
It has been shown that hydrogel bilayered scaffolds combining cartilage- and bone-like layers are most advantageous for treating osteochondral defects. In this study, it is proposed the use of low acyl gellan gum (LAGG) for developing bilayered hydrogel scaffolds for osteochondral tissue engineering. The cartilage-like layer of the GG-based bilayered hydrogel scaffolds is composed of LAGG (2 wt%). By adding a 2 wt% LAGG aqueous solution to different amounts of HAp (5-20 wt%) it was possible to produce the bone-like layer. In vitro bioactivity tests were performed by means of soaking the LAGG/LAGG-HAp hydrogel scaffolds in a simulated body fluid solution up to 14 days. Scanning electron microscopy, Fourier transform infra-red spectroscopy and X-ray diffraction analyses demonstrated that apatite formation is limited to the bone-like layer of the LAGG/LAGG-HAp bilayered hydrogel scaffolds.